PENGARUH MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA TERHADAP MINAT BELAJAR MAHASISWA STKIP PASUNDAN - Karwati, Euis (STKIP Pasundan, 2015)
STKIP Pasundan is a college that focuses on produce educators and education personnel. Based on observations and interviews obtained findings that college students at STKIP Pasundan have a low interest in learning. Media learning based on multimedia is believed to increase the interest of college students at STKIP Pasundan to learn. This study aims to know how the media learning based on multimedia, how the college students interest in learning, and also to analyze was there any influence frommedia learning based on multimedia to college students interest in learning at STKIP Pasundan. The method usedisdescriptive and verification. The sample was 120 collegestudents of STKIP Pasundan. The sampling technique used simple random sampling(SRS). Research instrument using a questionnaire. Analysis using linear regression analysis that used SPSS version 21. Based on these results,it canbe concluded that the media learning based on multimedia is in the high category, while college students interest in learning is in the medium category. In addition, the obtained findings that media learning based on multimedia has positive and significant impact on college students interest in learning. Thus, the media learning based on multimedia needs to be improved because it proved able to increase the college students interest in learning at STKIP Pasundan